Respons Pertumbuhan Rimpang Bangle (Zingiber purpureum) Pada Perlakuan PGPR (Plant Growth Promoting Rhizobacteria) - Wardana, Singgih Tri; Mangandi, Wulan Fransisca; Harmida, Harmida; Setiawan, Doni (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Bangle (Zingiber purpureum Rosc.) is one of the species of the Zingiberaceae family that has medicinal properties. Secondary metabolites contained in bangle rhizomes have biological activity as antioxidants, anti-inflammatory, anticancer, anti-asthma, anti-aging, neuroprotective, antimicrobial. Environmentally friendly technological innovation to increase soil nutrient content and plant growth in sustainable plant cultivation efforts is by utilizing plant growth-promoting rhizobacteria (PGPR). This study aims to determine the effect of PGPR concentration on the growth of bangle rhizomes. This study was conducted at the Physiology and Development Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University. A completely randomized study design was used with five PGPR concentration treatments (0; 75; 125; 175; and 225 ppm). Data were analyzed by Analysis of Variance (Anova) and Duncan’s Multiple Range Test (DMRT). The study showed that PGPR treatment can increase the growth of bangle rhizomes compared to no PGPR treatment. The best results at a PGPR concentration of 175 ppm in increasing the growth of bangle rhizomes.